2013
DOI: 10.1159/000345950
|View full text |Cite
|
Sign up to set email alerts
|

Systolic, Diastolic and Mean Arterial Pressure at 30-33 Weeks in the Prediction of Preeclampsia

Abstract: Objective: To investigate the potential value of measuring mean arterial pressure (MAP), systolic (sBP) and diastolic (dBP) blood pressure at 30-33 weeks' gestation in the prediction of preeclampsia (PE) developing at or after 34 weeks. Methods: Screening study in singleton pregnancies at 30-33 weeks' gestation including 4,294 that were unaffected by PE, gestational hypertension (GH) or delivery of small-for-gestational-age neonates (normal group), 145 that subsequently developed PE [37 cases requiring deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
1
25
0
1
Order By: Relevance
“…This research has already started. This issue of Fetal Diagnosis and Therapy publishes four studies performed by the Fetal Medicine Foundation which provide important evidence supporting that prediction of late-onset PE is possible by means of either uterine artery Doppler or angiogenic factors [9,10,11,12]. These results are in line with another very recent study from the United States [13].…”
supporting
confidence: 65%
“…This research has already started. This issue of Fetal Diagnosis and Therapy publishes four studies performed by the Fetal Medicine Foundation which provide important evidence supporting that prediction of late-onset PE is possible by means of either uterine artery Doppler or angiogenic factors [9,10,11,12]. These results are in line with another very recent study from the United States [13].…”
supporting
confidence: 65%
“…Recently it has been shown that uterine artery Doppler indices in the third trimester might be of clinical value [40][41][42][43][44]. Some studies have suggested that the predictive value of third trimester uterine artery Doppler is comparable to that of umbilical artery Doppler when predicting adverse pregnancy outcomes in late onset FGR [45][46][47].…”
Section: Uterine Artery Dopplermentioning
confidence: 99%
“…Two previous screening studies at 30-33 weeks' gestation examined 4,855 pregnancies and reported that at FPR of 5% screening by a combination of maternal characteristics and uterine artery PI or MAP detected 49 and 57%, respectively, of intermediate PE requiring delivery at 34-37 weeks and 37 and 49% of late PE with delivery at ≥38 weeks [27,28]. In the present extended series, we used a survival time model to treat gestational age at delivery for PE as a continuous, rather than categorical variable, allowing estimation of performance of screening for any desired interval between screening and delivery.…”
Section: Discussionmentioning
confidence: 99%